Methods of organizing special strength training for young short-distance runners in a one-year training macrocycle - Yuanquan, P.; Khorshidahmed, P.; Vrublevskiy, E. P. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to develop and substantiate a methodology for organizing special strength training for short-distance runners aged 14-15 years in an annual training cycle.